Assessing The Impact Of Toxic Toys On Indoor Environments And Children Health In Interior Decoration - Raj S, Ramesh; Raphella, S. Angel; Sundari, C. Aruna; Sivakami, P. (Journal of Neonatal Surgery, 2025)
The integration of decorative toys into interior spaces has become a popular trend, especially in settings designed for children. However, many of these toys contain toxic substances such as lead, phthalates, and volatile organic compounds (VOCs), which can pose significant health risks and degrade indoor air quality. This research explores the impact of toxic toys in interior decoration, focusing on their chemical composition, the potential health hazards they introduce, and their long-term effects on indoor environments. By analyzing case studies, scientific reports, and regulatory guidelines, the study aims to highlight the dangers associated with toxic decorative elements and propose safer alternatives for sustainable and health-conscious interior design. The findings will contribute to raising awareness among consumers and designers, advocating for stricter regulations and promoting the use of non-toxic materials in decorative aesthetics It is well knowledge that heavy metals like lead and cadmium delay brain development and increase the likelihood of high blood pressure. Because children's bodies absorb heavy metals more quickly than adults', they are the most vulnerable demographic. Such exposure might endanger their brain development. The toys include phthalates, which aid in the flexibility and dependability of plastic toys. the primary data is collected and the impact of toxic toys is examined by various tools using SPSS 27.0 and AMOS software. The media has to create awareness about the toxicity of toys and further plastic items to the public belonging to both urban and rural sectors